204k views
5 votes
Please help me on this

Please help me on this-example-1
User MTT
by
5.5k points

1 Answer

4 votes

Answer:

Option d


(2√(5)-4)(3√(5)+2)=22 -8√(5)

Explanation:

We have an expression composed of the product of 2 factors:


(2√(5)-4)(3√(5)+2)

To simplify the expression we use the distributive property


(2√(5)-4)(3√(5)+2) = 2√(5)(3√(5)) +2√(5)(2) -4(3√(5)) -4(2)

Simplifying we obtain:


(2√(5)-4)(3√(5)+2)=6(5) +4√(5) -12√(5) -8\\\\(2√(5)-4)(3√(5)+2)=30 -8√(5) -8\\\\(2√(5)-4)(3√(5)+2)=22 -8√(5)

The answer is the option d.

User Justdvl
by
5.5k points